(untitled) (Asian Business Research, 2017)
In this paper is described the explanation of the real reasons for the financial crise in Greece based on the Lord Prof PhD PhD Momtchil Dobrev-Halachev developed 2008 “Theory of generating of crises “ and 2001 “ Theory of the mafia”. Based on these two theories this paper explane the establishment of the financial crises 2008 all over the world (Dobrev, 2015). Lord prof PhD PhD Momtchil Dobrev-Halachev developed 2008 “Theory of generating of crises “and 2001 “ Theory of the mafia”. Based on these two theories this paper explane the establishment of the financial crises in Greece.